2017
DOI: 10.1515/revce-2016-0040
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen applications and research activities in its production routes through catalytic hydrocarbon conversion

Abstract: AbstractThe statistical information on the share of hydrogen sector-wise consumption indicates that 95% of the total consumption is utilized in ammonia synthesis, petroleum refining processes and methanol production. We discuss how hydrogen is used in these processes and in several smaller-scale manufacturing industries. We also present the trend of hydrogen used as fuel, and as an energy carrier in fuel cells for generating electricity, powering hydrogen vehicles, as well as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 92 publications
0
15
0
Order By: Relevance
“…The utilization of BMC as the catalysts has been demonstrated in the hydrocarbon decomposition reaction to produce carbon nanomaterials and hydrogen. Chinthaginjala et al (2008) demonstrated hydrocarbon decomposition, which is also a catalytic route to produce hydrogen (Baharudin and Watson 2017), for carbon nanofibers (CNF) synthesis over a Ni foam as the BMC. The growth of CNF took place on the BMC itself.…”
Section: Classification Of Monolithic Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of BMC as the catalysts has been demonstrated in the hydrocarbon decomposition reaction to produce carbon nanomaterials and hydrogen. Chinthaginjala et al (2008) demonstrated hydrocarbon decomposition, which is also a catalytic route to produce hydrogen (Baharudin and Watson 2017), for carbon nanofibers (CNF) synthesis over a Ni foam as the BMC. The growth of CNF took place on the BMC itself.…”
Section: Classification Of Monolithic Catalystsmentioning
confidence: 99%
“…It is the most common pathway for producing hydrogen and synthesis gas (syngas, i.e. hydrogen + carbon monoxide) due to its cost effectiveness (Mohammadzadeh and Zamaniyan 2002, Zamaniyan et al 2011, Saito et al 2015 as compared to other processes discussed by Baharudin and Watson (2017). In this review paper, a monolithic structured packing for steam methane reforming (SMR) reactor will be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Among other possible energy systems, hydrogen (H 2 ) as an energy carrier is considered a potentially viable solution to address sustainable energy production, when coupled with renewable sources and adequate technology [1][2][3][4]. H 2 gas is an ideal energy carrier for a number of applications [5][6][7]; it can be produced using a range of technologies [8][9][10][11], and of those, the non-carbon based hybrid sulphur (HyS) cycle is a potential large-scale H 2 production process [12,13]. In this cycle, sulphuric acid (H 2 SO 4 ) is thermally (>800 • C) decomposed into water (H 2 O), oxygen (O 2 ), and sulphur dioxide (SO 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Direct application of hydrogen is in internal combustion engines [50] and fuel cells [51]. Indirectly hydrogen is used to produce liquid fuel [52], methanol [53], and upgrading of heavy crude oil and bitumen [54].…”
Section: Syngas To Hydrogenmentioning
confidence: 99%